The study of glucose-6-phosphate dehydrogenase (G6PD) gene by restriction enzyme by restriction enzyme digestion in the Kelantan population - Yusoff, Narazah Mohd; Jamaluddin, Normah; Hussin, Zabidi Azhar Mohd; Ee, Choo Keng; Sein, Kyaw Tun
The most common diseases producing enzymopathy affecting the human population is glucose-6-phosphate dehydrogenase (G6PD) deficiency. It is estimated that about 400 million people worldwide are affected and this disease is commonest seen in the tropical and subtropical zones of the Eastern hemisphere. Molecular analysis has confirmed that the basis for G6PD deficiency is widely heterogeneous. Different mutants are responsible for the G6PD deficiency in the various parts of the world where this abnormality is prevalent. This study involved a sequential analysis whereby the blood from Malay neonates with neonatal jaundice admitted to Hospital Universiti Sains Malaysia and Kota Bharu Hospital were analyzed and polymerase chain reaction based analysis using serial multiplex primer method was done on those DNA samples. Samples that are found to be abnormal were then sequenced. Out of the 45 samples studied, 8 were found to have the Mediterranean mutation, two have the Mahidol mutation, two have Canton mutation and three have Kaiping mutation. Thus the molecular basis for the Malay neonatal jaundice in Kelantan is described with further prospect of population screening.